Current guidance underestimates risk of global environmental change to food security - Myer, Samuel; Fanzo, Jessica; Wiebe, Keith D.; Huybers, Peter; Smith, Matthew R. (BMJ, 2022)
Over the past several years many global reports and scientific articles have offered guidance to policy makers on how climate change is likely to affect global food security. But these publications paint an incomplete, and likely overly optimistic, picture of the threat that anthropogenic environmental change poses to food production, nutrition, and health. Projected effects of climate change on food security are often based on crop models that incorporate only a few dimensions of climate related biophysical change—usually characterized by changes in temperature and precipitation. Omitted from these mathematical models are other biophysical changes related to a disrupted climate system and, importantly, other anthropogenic biophysical changes that are also likely to affect the quality or quantity of food the world can produce.